Particulate Matter Fluxes in a Mediterranean Mountain Forest: Interspecific Differences Between Throughfall and Stemflow in Oak and Pine Stands. Issue 9 (7th May 2019) - Cayuela, Carles; Levia, Delphis F.; Latron, Jérôme; Llorens, Pilar
Abstract: In forested areas, canopies play an important role in the partitioning of rainfall. During this process there is also a redistribution of particulate matter (PM) that is deposited from the atmosphere on vegetative surfaces and transported to soil layers by throughfall and stemflow. We collected samples of rainfall, throughfall, and stemflow from two different forest plots (pine and oak) in a Mediterranean mountainous area and analyzed the amount and size distributions of PM (0.45 μm < PM < 500 μm). The exploration of backward trajectories revealed that PM content varied significantly. This depended on the origin of the air mass, with Atlantic fronts transporting less PM in the atmosphere than North African dust intrusions, which added disproportionate inputs of PM. Overall, throughfall provided the largest proportion of incoming PM under trees, but, at the base of each tree, stemflow led to a localized input of water that was more PM enriched than water through open precipitation or throughfall. Interspecific differences in PM fluxes were noted with pines retaining more PM in their crowns than oaks. Furthermore, the presence of leaves on oak increased the size and the amount of particulates released by throughfall. The PM in stemflow was smaller and rounder than in throughfall. This study adds to our understanding knowledge of the processes that control the deposition and distribution of PM delivered to forest soils, a fraction that is often ignored in studies of nutrient and energy fluxes in ecosystems. Key Points: Atmospheric particulate matter was highly influenced by Saharan dust intrusions despite accounting for only 16% of the events Canopies enhanced the concentration of particulate matter in throughfall and stemflow, but stemflow had higher enrichment ratios Leaf presence or absence influenced the size of the particulate matter, although the smallest particulates were measured in stemflow